2019
DOI: 10.29219/fnr.v63.1577
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antimicrobial, and antiproliferative activity-based comparative study of peel and flesh polyphenols from Actinidia chinensis

Abstract: Background Kiwifruit ( Actinidia chinensis ) peel has been always considered as useless because of the harsh taste. To promote the full utilization of kiwifruit resources it is essential to explore the nutritional benefits of kiwifruit peel. Objective Our studies explored the difference in polyphenolic composition and biological activity including antioxidant, antimicrobial, and antiproliferative activity of the flesh and peel of kiwifruit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
(41 reference statements)
2
26
2
2
Order By: Relevance
“…Catechin as one main content in our study is consistent with previous report. Alim et al () found that the main compounds also included quercetin and epigallocatechin. Several factors can influence the phytochemicals contents such as cultivars, the degree of fruit ripening, environmental conditions, and the extraction methods (Zhu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catechin as one main content in our study is consistent with previous report. Alim et al () found that the main compounds also included quercetin and epigallocatechin. Several factors can influence the phytochemicals contents such as cultivars, the degree of fruit ripening, environmental conditions, and the extraction methods (Zhu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Catechin as one main content in our study is consistent with previous report. Alim et al (2019) found that the main compounds also included quercetin and epigallocatechin.…”
Section: Hplc Analysismentioning
confidence: 99%
“…Various studies have examined the antioxidant activity of both peel and lesh of kiwi fruit in different in-vitro assay systems (Zuo et al, 2012). In most cases, the kiwi fruit extract showed moderate antioxidant activity, but the peel extract seemed to have more polyphenols and lavonoids which in turn have high antioxidant activity than the lesh of the fruit (Alim et al, 2019). The study illustrated that Actinidia chinensis peel was found to have a greater number of speci ic polyphenols and lavonoids, which are responsible for the higher antioxidant, antimicrobial, and antiproliferative activity when compared to the lesh of the fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Kiwi fruit is distinct for its soft texture and its unique lavours. Comparative studies on kiwi fruit peel and its lesh have been conducted (Alim et al, 2019). The peel of kiwifruit was identi ied to have a high content of phenolics and lavonoids; and exerts more potent antioxidant, antibacterial and anticancer activity than its lesh.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan peranan yang cukup besar dari buah kiwi yang diantaranya membantu proses debridement dan pelepasan jaringan parut tanpa merusak proses penyembuhan, perbaikan angiogenesis, epitelisasi dan granulasi, serta efeknya terhadap penurunan ukuran luka menunjukkan bahwa buah kiwi dapat menjadi pilihan pengobatan yang menjanjikan bagi upaya terapi luka bakar (Pisoschi et al, 2015). Penelitian lain yang dilakukan oleh Alim et al (2019) aktivitas antibakterial yang lebih signifikan ketika menggunakan balut buah kiwi dibandingkan dengan pemberian sulfadiazine silver pada hewan yang dicobakan. Mohajeri dkk mengindikasikan bahwa pembalutan dengan buah kiwi mempercepat penyembuhan luka pada luka bakar dan mereka menyatakan efek ini berasal dari antibakterial yang dramatis.…”
Section: Hasil Dan Pembahasanunclassified